PERANAN PENGURUS POKJAR UPBJJ-UT PEKANBARU DALAM MEMPROMOSIKAN UNIVERSITAS TERBUKA - Devi, Shanti; Usman, Raja (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2010)
Students at Universitas Terbuka especially from Primary Schools Teachers Education program are clustered into study groups. These study groups exist in all UT regional centers. Several study groups are coordinated by a coordinator. The coordinators have important role in managing the students learning activities as well as promoting Universitas Tebuka. Charcteristics of coordinators, factors related to coordinators roles, and their involvement in promoting UT are discussed in this article.